2006
DOI: 10.1080/13691060600572557
|View full text |Cite
|
Sign up to set email alerts
|

Financing of women-owned ventures: The impact of gender and other owner -and firm-related variables

Abstract: While women-owned ventures represent an increasing proportion of new businesses in most western countries, most of them have particular financing patterns and encounter barriers in their access to financing. Recent research on the question argues that barriers to financing are mainly dependent on factors other than gender, such as owner-and firm-related characteristics. This quantitative and qualitative study, through descriptive statistics and interview analysis, examines the relationship between financing pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 25 publications
5
85
2
5
Order By: Relevance
“…When they categorized the firms by growth potential, the authors found that women in high growth or traditionally male-dominated lines of business encountered fewer gender-related barriers to borrowing than women in more traditional service or retail lines of business. Constantinidis et al (2006) found a high level of risk aversion in the women entrepreneurs they interviewed and concluded that women may choose lifestyle types of businesses to balance family and business demands and to avoid dependence on external sources of capital.…”
Section: Debt Financingmentioning
confidence: 99%
See 3 more Smart Citations
“…When they categorized the firms by growth potential, the authors found that women in high growth or traditionally male-dominated lines of business encountered fewer gender-related barriers to borrowing than women in more traditional service or retail lines of business. Constantinidis et al (2006) found a high level of risk aversion in the women entrepreneurs they interviewed and concluded that women may choose lifestyle types of businesses to balance family and business demands and to avoid dependence on external sources of capital.…”
Section: Debt Financingmentioning
confidence: 99%
“…Similarly, women were no less likely to be approved once they had applied for a loan. Constantinidis et al (2006) found differences in both demand and supply side patterns when they studied women entrepreneurs in Belgium. Ironically, although 86% of their loan requests were approved, almost 50% of the women surveyed indicated that they experienced barriers in their attempts to secure loans.…”
Section: Debt Financingmentioning
confidence: 99%
See 2 more Smart Citations
“…Dong and Men (2014) and Abor et al (2014) consider the limited access to external financing including bank loans as one of SMEs growth obstacle. Several other authors like Garwe and Fatoki (2012), Roper and Scott (2009), Mijid (2009), Constantinidis et al (2006), Zwan et al (2010), Mama and Ewoudou (2010), Freel et al (2010), Nkundabanyanga et al (2014), Ključnikov and Belás (2016) and Krasniqi (2010), etc. devote their attention to this topic.…”
Section: Literature Reviewmentioning
confidence: 98%